The Building’s Visual Character Framer on Apartment-Mall-Rental Office Mixed Use Building Design Study in Banjarmasin City - Muhammad Isfan Noverizal; Hestin Mulyandari (University of Technology Yogyakarta, 2022)
By the fast development of society needs, society service facility to accommodate those need is also developing, mixed use building is a building which be able to society activities, with the building façade as the identity of each function within, which present the building image. Façade is front appearance or outside building which reflect the building image with aesthetic element, resulting on the meaning of the mixed use building function. The uneven appearance of the building can cause the low quality of building’s visual character. The research method uses descriptive research methods, which analyze visual character on mixed use building, which include three different function. On those three building characteristic function, unity character on building visual character is taken, so that it can be used as standard design criterion in order to another new building can be built fairly with the existing building which then strengthen the zone identity. The existence of unity on the visual character on those three buildings with entrance, opening, ornament and roof components, and the other character consist of symmetric rhythm, geometry, proportion scale, color and material composition.